Trends in shooting results of elite biathletes - Cholewa, J.; Gerasimuk, D.; Zajac, A. (Journal of Human Kinetics, 2004)
The authors of this paper attempted to estimate the value and direction of biathlon shooting tendencies in particular events and shooting positions. Shooting results of 190 competitors who took part in World Cups, World Championships and Olympic Games from 1997/98 to 2003/04 seasons were analyzed statistically. The data indicates that shooting results during the analyzed period had a tendency to decrease. This is especially true in relay competition (annual decrease of specified variable is 0.9%, R2=0.60) and in the prone shooting position (annual decrease of specified variable is 0.5-0.6%, R2=0.51).